Subradiographic foot and ankle fractures and bone contusions detected by MRI in elite ice hockey players - Baker J. C.; Hoover, E. G.; Hillen, T. J.; Smith, M. V.; Wright, R. W.; Rubin, D. A. (The American Journal of Sports Medicine, 2016)
Background: In ice hockey players, serious bone injuries in the foot and ankle, especially those attributed to impact from the moving puck, may be radiographically occult and underrecognized. Purpose/Hypothesis: The purpose of this research was to study foot and ankle bone injuries detected with magnetic resonance imaging (MRI) that occurred in elite hockey players. The hypothesis was that these injuries predominate medially, especially when caused by the impact from the puck, and are associated with prolonged lost playing time. Study Design Case series; Level of evidence, 4. Methods: Three independent observers, blinded to the mechanism of injury, retrospectively reviewed foot and ankle MRI examinations acquired after 31 acute injuries that occurred in 27 elite ice hockey players who had no radiographically visible fractures. Bone abnormalities were classified as fractures or varying degrees of contusion based on predetermined definitions. Interobserver agreement was analyzed with kappa statistics. The association between the injury mechanism and the bones involved was examined with the Fisher exact test. A t test was applied to determine if MRI evidence of a severe bone injury (defined as either a fracture or a high-grade bone contusion) was associated with longer recovery times, when return-to-play information was available. Results: The observers identified at least 1 bone injury in 27 of the 31 MRI examinations, including 10 with radiographically occult fractures. Agreement among the 3 observers for injury categorization was substantial (? = 0.76). Seventeen injuries were caused by a direct blow (15 from a moving puck, 2 from an uncertain source), resulting in 6 fractures and 6 high-grade bone contusions, with 14 of the 17 involving a medial bone (medial malleolus, navicular, or first metatarsal base). Compared with other mechanisms, direct impaction was statistically more likely to result in a severe bone injury and to involve the medial foot and ankle. In 20 injuries where return-to-play information was available, players with severe bone injuries missed a mean of 10.6 games compared with 2.4 games for other players (P = .05). Conclusion: MRI can show severe bone injuries that are not visible radiographically in ice hockey players. Most fractures and high-grade contusions involve the medial ankle and midfoot bones, can be caused by direct blows from the puck, and are associated with prolonged recovery times.